Implementasi Peran dan Fungsi Satuan Polisi Pariwisata Polda Metro Jaya - Monica Margaret (Deviance Jurnal kriminologi, 2017)
The establishment of special police units such as Polda Metro Jaya Police Tourism Units should have specificity as well as in the execution of their roles and functions. However, in this research, there are still execution of common police tasks such as traffic arrangement which is the task of Traffic Police Unit, then security on the demonstration activities that are the responsibility of Samapta Police Unit and also there are still obstacles that become less value against Imaging that want to be realized by Polda Metro Jaya Tourism Police Unit. Qualitative research with descriptive approach through this observation describes the role and function of Polda Metro Jaya Police Tourism Unit related to the concept of community policing, problem solving and public service. This study obtained data that the Police Tourism Police Unit Metro Jaya has the role and function to conduct security on tourist objects including the mobility of tourists who require special security conducted in the form of activities such as providing services in the form of guidance and counseling to the community, especially to foreign tourists As well as domestic such as providing information on the location of tourist attractions, means of transportation, hospitality and places of entertainment; Carry out arrangements when finding traffic congestion especially in the area of the tourist location for which it is responsible; Guarding tourism objects conducting activities of the crowd or obtaining state visits; Carry out patrols / visits to the areas for which it is responsible; Then carry out the first act on the scene.